Contributive Role of TNF-α to L-DOPA-Induced Dyskinesia in a Unilateral 6-OHDA Lesion Model of Parkinson’s Disease - dos Santos Pereira, Maurício; Abreu, Gabriel Henrique Dias; Rocca, Jeremy; Hamadat, Sabah; Raisman-Vozari, Rita; Michel, Patrick Pierre; Del Bel, Elaine (Frontiers in Pharmacology, 2021)
Our present objective was to better characterize the mechanisms that regulate striatal neuroinflammation in mice developing L-DOPA-induced dyskinesia (LID). For that, we used 6-hydroxydopamine (6-OHDA)-lesioned mice rendered dyskinetic by repeated intraperitoneal injections of 3,4-dihydroxyphenyl-L-alanine (L-DOPA) and quantified ensuing neuroinflammatory changes in the dopamine-denervated dorsal striatum. LID development was associated with a prominent astrocytic response and a more moderate microglial cell reaction restricted to this striatal area. The glial response was associated to elevations in two pro-inflammatory cytokines, tumor necrosis factor-α (TNF-α) and interleukin-1β. Treatment with the phytocannabinoid cannabidiol and the transient receptor potential vanilloid receptor 1 (TRPV-1) antagonist capsazepine diminished LID intensity and decreased TNF-α levels without impacting other inflammation markers. To possibly reproduce the neuroinflammatory component of LID, we exposed astrocyte and microglial cells in culture to candidate molecules that might operate as inflammatory cues during LID development, i.e., L-DOPA, dopamine, or glutamate. Neither L-DOPA nor dopamine produced an inflammatory response in glial cell cultures. However, glutamate enhanced TNF-α secretion and GFAP expression in astrocyte cultures and promoted Iba-1 expression in microglial cultures. Of interest, the anti-dyskinetic treatment with cannabidiol + capsazepine, reduced TNF-α release in glutamate-activated astrocytes. TNF-α on its own, promoted synaptic release of glutamate in cortical neuronal cultures, whereas cannabidiol + capsazepine prevented this effect. Therefore, we may assume that the release of TNF- by glutamate-activated astrocytes may contribute to LID by exacerbating corticostriatal glutamatergic inputs excitability and maintaining astrocytes in an activated state through a self-reinforcing mechanism.